IFNγ-Stimulated B Cells Inhibit T Follicular Helper Cells and Protect Against Atherosclerosis - Douna, Hidde; de Mol, J.; Amersfoort, Jacob; Schaftenaar, Frank H.; Kiss, Mate G.; Suur, Bianca E.; Kroner, Mara J.; Binder, Christoph J.; Bot, Ilze; Van Puijvelde, Gijs H. M.; Kuiper, Johan; Foks, Amanda C. (Frontiers in Cardiovascular Medicine, 2022)
B and T cells are interconnected in the T follicular helper—germinal center B cell (TFH-GC B cell) axis, which is hyperactive during atherosclerosis development and loss of control along this axis results in exacerbated atherosclerosis. Inhibition of the TFH–GC B cell axis can be achieved by providing negative co-stimulation to TFH cells through the PD-1/PD-L1 pathway. Therefore, we investigated a novel therapeutic strategy using PD-L1-expressing B cells to inhibit atherosclerosis. We found that IFNγ-stimulated B cells significantly enhanced PD-L1 expression and limited TFH cell development. To determine whether IFNγ-B cells can reduce collar-induced atherosclerosis, apoE−/− mice fed a Western-type diet were treated with PBS, B cells or IFNγ-B cells for a total of 5 weeks following collar placement. IFNγ-B cells significantly increased PD-L1hi GC B cells and reduced plasmablasts. Interestingly, IFNγ-B cells–treated mice show increased atheroprotective Tregs and T cell-derived IL-10. In line with these findings, we observed a significant reduction in total lesion volume in carotid arteries of IFNγ-B cells-treated mice compared to PBS-treated mice and a similar trend was observed compared to B cell-treated mice. In conclusion, our data show that IFNγ-stimulated B cells strongly upregulate PD-L1, inhibit TFH cell responses and protect against atherosclerosis.